A Taphonomic Study of Crocodylus porosus (Crocodylidae) and Tomistoma schlegelii (Gavialidae) Remains from Western Sarawak, Malaysian Borneo: Applications for Public Education - Hassan, Ruhana; Mohd Azizi, Nur Fatimah; Md Adzhar, Muhammad Amirul Arib; Abdul Gani, Mohd Izwan Zulaini; Ahmad, Rambli; Moi Ung, Charles Leh (Trends in Undergraduate Research, 2018)
This study documented details of the dentitions, skulls and other skeletal remains of Crocodylus porosus and Tomistoma schlegelii, from western part of Sarawak, Malaysian Borneo. The remains of both reptiles were exhumed, followed by standard cleaning procedures and then detail morphological assessments were carried out accordingly. Both species show similar structure of vertebral columns, but T. schlegelii has the following unique structures: a long and narrower snout, D-shaped eye sockets, long and sharp pointed protruding quadratojugal bones, straight maxillae and dentary, a smooth surfaced skull, elongated triangular suborbital fenestrae, round shaped internal nares and visible supraoccipital from a dorsal view. C. porosus has heterodont dentition with blunt-pointed and irregular size of teeth whereas T. schlegelii has almost homodont dentition with sharp and similar size teeth. This is the first collection of teeth, skulls and other skeletal remains of both species obtained from Sarawak, and the materials have been used regularly to educate the public through science exhibitions, hoping they will spark the interests of young budding scientists to be involved in wildlife taphonomic studies in the future. Keywords: Crocodylus porosus, dentition, reptile, skeletal remain, Tomistoma schlegelii